'Left with a title but nothing else': the challenges of embedding professional recognition schemes for teachers within higher education institutions. Issue 6 (19th September 2019) - Spowart, Lucy; Winter, Jennie; Turner, Rebecca; Burden, Penny; Botham, Kathryn Ann; Muneer, Reema; van der Sluis, Hendrik; Huet, Isabel
ABSTRACT: With increasing moves globally towards the professionalisation of teaching in Higher Education, there is growing interest in the role of accredited professional recognition schemes that provide professional development for established university teaching staff. In the UK, There are now over 120 professional recognition schemes, resulting in institutionally focused evaluation studies examining their impact. This article contributes to this emerging body of work; it draws on cross-institutional data and Foucauldian theorising to address two important questions. In what ways does engagement with an institutional professional recognition scheme impact on participants' teaching development, and how does institutional culture influence that engagement? The data illustrate that whilst institutional culture drives engagement, it did little to promote teaching development. Across the case-study institutions, neo-liberalism agendas were apparent. Some staff felt pushed to achieve professional recognition in response to the increasing use of metrics to measure the student experience and to inform institutional standing in league tables. Whilst evidence shows the process of seeking accreditation can lead to an enhancement in teaching practices, caution must be taken to ensure that the professional development opportunities offered by accreditation schemes are fully realised.